Social frustratedness as a psychogenesis factor of adjustment disorders - L. I. Wasserman; O. Yu. Shchelkova; E. A. Dubinina; M. A. Berebin; V. A. Mikhailov; E. A. Nikiforova; D. N. Chugunov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
Summary. The current biopsychosocial paradigm in medicine and medical psychology ensures the development of the theory and methodology of medical psychodiagnostics as a comprehensive study of psychological and psychosocial factors underlying mental adaptation. The diagnostic of prenosological and initial manifestations of borderline spectrum disorders designated as adjustment disorders in ICD-10 (F43.2), requires the criteria qualification of real or potential stressogenic social functioning conditions, thus, an arsenal of adequate methods of clinical and medical-psychosocial psychodiagnostics is required. The questionnaire «Social Frustration Level» represents one of such methods. The study of social frustration phenomenon as a predictor of emotional tension and stress resistance allows to characterize personality traits in relation to environmental influence and assess the specificity and pathogenic significance of socially frustrating factors. The article substantiates theoretical and methodological foundations of the questionnaire, its attributive characteristics — the phenomena of external and internal social frustration identified in medical psychodiagnostics for the first time. Socio-diagnostic criteria are illustrated by examples of the practical use in medical psychodiagnostics of social frustration in teachers of mass schools, the military and in patients with focal epilepsy. The specified research contingent is united by the problem of stress resistance in crisis situations (including a disease situation and the attitude to the disease). The questionnaire «Social Frustration Level» can be considered as a necessary form of psychosocial diagnostics of stress genesis, a source of information in screening psychoprophylactic studies, as well as in the forming of indications for psycho- and sociotherapy.